2018
DOI: 10.1029/2018jc014100
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Eddy Generation in the Central Bay of Bengal

Abstract: Eddy activity in the central Bay of Bengal (BoB) is revealed using satellite observations and hydrographic data. Altimetric data show that eddies are generated near the eastern boundary, propagate southwestward, and have periods predominantly in the 30-to 120-day band. Temperature profiles from the Research Moored Array for African-Asian-Australian Monsoon Analysis and Prediction (RAMA) buoy at 90°E, 15°N, have their highest amplitude in the depth range of the thermocline, indicating that the eddies are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 29 publications
7
72
0
1
Order By: Relevance
“…The number of CEs was approximately 17% higher than that of AEs, and their mean lifespans were approximately 57 days and 56 days, respectively. Consistent with previous studies [14,[16][17], eddy-rich regions with more than four CEs and AEs in each 1 ° bin were observed to be located at the western boundary, the northern bay, and the Andaman Sea (Figure 3a, b). The mean amplitudes of the CEs and AEs show a similar spatial pattern (Figure 3c,d).…”
Section: Eddy Statisticssupporting
confidence: 91%
See 2 more Smart Citations
“…The number of CEs was approximately 17% higher than that of AEs, and their mean lifespans were approximately 57 days and 56 days, respectively. Consistent with previous studies [14,[16][17], eddy-rich regions with more than four CEs and AEs in each 1 ° bin were observed to be located at the western boundary, the northern bay, and the Andaman Sea (Figure 3a, b). The mean amplitudes of the CEs and AEs show a similar spatial pattern (Figure 3c,d).…”
Section: Eddy Statisticssupporting
confidence: 91%
“…In addition, another critical region for eddy generation is located at the eastern boundary over the BOB, according to altimeter measurements [14,[16][17]. The equatorial wind forcing and the instability triggered by the Myanmar bump are the two major reasons for eddy formation in that area [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Cheng et al . 12 showed that the Rossby waves, radiated out from the coastal Kelvin wave, get significantly altered by the ANIs and increase eddy activity in the central BoB. But, their analysis was restricted only in the central and eastern BoB (east of 85°E).…”
Section: Introductionmentioning
confidence: 99%
“…Again, the median radius of these eddies is nearly equal for AEs and CEs (~100 km), but CEs have a much larger range reaching up to 192 km. The largest amplitude eddies tended to generate in the western Bay (Figure 1), where baroclinic instability of the EICC helps generates eddies (Cheng et al, 2018), so their trajectories follow this current (Figures 7g and 7h). In the EICC region, there is a higher concentration of AEs.…”
Section: 1029/2020jc016772mentioning
confidence: 99%